Late Antiquity: concepts and history from a Brazilian perspective - Ramalho, Jefferson (Romanitas - Revista de Estudos Grecolatinos, 2016)
Review of: FUNARI, Pedro Paulo A.; CARLAN, Cláudio Umpierre. Antiguidade Tardia e o fim do Império Romano no Ocidente. São Paulo: Fonte Editorial, 2016. 116 p.